TEORI KESAN PERTAMA TERHADAP PESAN VISUAL POSTER KAMPANYE DALAM KEPUTUSAN PEMILU 2024 - Arif Billah, Syamsul; Ayu Wulandari, Ajeng; Sapitri, Ade Novi (LPPM Universitas Adhirajasa Reswara Sanjaya, 2024)
In an era characterized by rapid information flow and advancing media technology, visuals play a pivotal role in shaping the image of legislative candidates and political parties in the eyes of voters. Campaign posters, as one of the primary visual communication tools, are widely employed to convey messages and cultivate positive perceptions of candidates. This study aims to analyze how visual elements in campaign posters, particularly the portrayal of candidate personality and branding messages, influence voter decisions in the 2024 General Elections. Utilizing a qualitative approach grounded in the First Impression Theory, the research explores how initial impressions formed from these visual elements can affect voter perceptions and choices. The findings indicate that aspects of candidate portrayal, such as facial expressions, attire, appearance, as well as contextual elements like symbols and iconography, along with clearly and attractively conveyed branding messages, significantly impact voter attention and decision-making. This study offers valuable insights into the role of visuals in contemporary politics and provides strategic perspectives for campaign teams to design more effective and competitive strategies in the future. The results also underscore the importance of maximizing visual communication in politics to influence election outcomes.